Karakterisering in Christine: ’n Jungiaanse perspektief - M. L. Crous (Literator, 1991)
The central character in Bartho Smit’s complex drama Christine is Paul Harmse. This essay focuses on the text and regards it as the psyche of the protagonist Paul Harmse. Jung’s theory of the collective unconscious and the archetypal figures that inhabit the collective unconscious is implemented in the analysis of the text. The characters are regarded as representations of the shadow and the anima. There is a prevailing conflict between Paul Harmse and the subconscious forces at work in his psyche.